2013
DOI: 10.4141/cjas2012-081
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects in broiler chickens fed a high lycopene concentration supplemented diet

Abstract: . 2013. Adverse effects in broiler chickens fed a high lycopene concentration supplemented diet. Can. J. Anim. Sci. 93: 231Á241. The present investigation was designed to assess the effects of the administration of a high dietary lycopene dose to broiler chickens on growth and slaughter performances, haematoÁbiochemical parameters, antioxidant enzymes, histological lesions and lycopene accumulation in the tissues. Thirty-six 1-d-old male Hubbard broiler chicks were examined and divided randomly into two groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…The results of this study revealed that dietary lycopene did not significantly improve production performance rates. This result is in accordance with the results obtained by Pozzo et al (2013). Interestingly, fertilization rates and hatchability of eggs set significantly (P < 0.05) increased with lycopene supplementation.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The results of this study revealed that dietary lycopene did not significantly improve production performance rates. This result is in accordance with the results obtained by Pozzo et al (2013). Interestingly, fertilization rates and hatchability of eggs set significantly (P < 0.05) increased with lycopene supplementation.…”
Section: Discussionsupporting
confidence: 82%
“…Findings from other studies reveal that lycopene improves the lipid profile of chickens (Sevcikova et al 2008). Meanwhile, negative effects of high doses of lycopene have been found in broiler chickens (Pozzo et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Growth performance is an indispensable indicator of poultry growth status under different conditions ( 21 ), and the lycopene could improve chicken performance ( 22 , 23 ). In the present study, the ADG increased, and the FCR decreased in groups treated with lycopene in the grower and whole phases, and the ADFI was quadratically affected by lycopene in the grower phase, which was consistent with Mezbani's study ( 22 ), who reported that chicken supplemented with 100 mg/kg lycopene from 21 to 42 days resulted in the increased body weight and decreased feed conversion ratio.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Sevcikova et al ( 2008 ) reported that dietary LP at 100 mg/kg of diet, but not at 50 mg/kg of diet, significantly increased the body weight in broiler chickens compared with those fed the LP-free diet. On the other hand, dietary LP failed to affect growth performance of broiler chickens fed diet containing tomato skin extracts, which contained 200 mg of LP per kg of diet (Marzoni et al 2014 ), or LP at 500 ppm (Pozzo et al 2013 ). Leal et al ( 1999 ) reported that LP feeding reversed the T-2 toxin-induced depression in feed intake and weight gain in chicken.…”
Section: Discussionmentioning
confidence: 99%
“…The latter finding explains the failure to find the presence of LP in leg meats compared with that in liver and plasma as shown in this study. Nonetheless, Pozzo et al ( 2013 ) reported that trace amounts of LP were detected in breast (0.10 mg/kg of fresh weight) and thigh meats (0.42 mg/kg of fresh weight) of broiler chickens fed LP-added diet at the level of 500 mg. Due to the lack of studies measuring LP in poultry meats, further studies with graded levels of LP are warranted to prove the observed differences. In contrast, the presence of LP in serum and liver has been well established in poultry (Sahin et al 2006 ; Englmaierova et al 2011 ; Sun et al 2014a , 2015 ), which corroborates well with our current study.…”
Section: Discussionmentioning
confidence: 99%